2003
DOI: 10.1007/s00423-003-0389-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective skeletal muscle arteriolar vasomotion during critical perfusion conditions of osteomyocutaneous flaps is not mediated by nitric oxide and endothelins

Abstract: Our study indicates that during critical perfusion conditions, arteriolar vasomotion develops only in muscle, not in skin, subcutis and periosteum, and that nitric oxide and endothelins are not involved in the regulation of this protective vascular response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…5 illustrate how type II swings only occur at frequencies Ͻ0.04 Hz whereas the type I swings occur at a range of frequencies up to 0.32 Hz. Our understanding of the nature and origin of rhythmic fluctuations in the cardiovascular system has been advanced with the development of optical tools such as laser Doppler fluximetry (27,40) and intravital microscopy (6,35,41). These techniques have studied the spontaneous rhythmic vasodilation and vasoconstriction of blood vessels, known as vasomotion, through the measurement of oscillations in the concentration of moving red blood cells (flux) or vessel diameter, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…5 illustrate how type II swings only occur at frequencies Ͻ0.04 Hz whereas the type I swings occur at a range of frequencies up to 0.32 Hz. Our understanding of the nature and origin of rhythmic fluctuations in the cardiovascular system has been advanced with the development of optical tools such as laser Doppler fluximetry (27,40) and intravital microscopy (6,35,41). These techniques have studied the spontaneous rhythmic vasodilation and vasoconstriction of blood vessels, known as vasomotion, through the measurement of oscillations in the concentration of moving red blood cells (flux) or vessel diameter, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that release of NO from nitrosyl-hemoglobin complexes improved local tissue perfusion in epigastric rat flaps [4]. In contrast to these findings, a protective arteriolar vasomotion in skeletal muscle during critical perfusion of osteomyocutaneous flaps in rats was reported to occur independently of NO [5]. Additionally, nitric oxide at high concentrations has also been reported to exert cytotoxic effects by direct toxicity or by reaction with superoxide.…”
Section: Introductionmentioning
confidence: 90%
“…This regulatory mechanism occurs only in the striated muscle, not in the periosteum, subcutis and skin; however, it secures not only muscle microvascular perfusion, but, by redistribution of blood flow, also maintains the microvascular perfusion of those tissues which are not capable of exerting this regulatory control under critical perfusion conditions [58]. More detailed analysis revealed that arteriolar vasomotion and capillary flow motion are calcium-dependent phenomena, independent from nerve innervation [58] and not influenced by the endothelinnitric oxide balance [59]. Interestingly, the regulatory control of vasomotion and flow motion under critical flap perfusion conditions is abrogated after free flap transfer, which may be related to the ischemia-reperfusion insult [60].…”
Section: The Saphenous Artery Osteomyocutaneous Flap Modelmentioning
confidence: 95%